BALF metagenomic next-generation sequencing analysis in hematological malignancy patients with suspected pulmonary infection: clinical significance of negative results - Deng, Zuqun; Tang, Yishu; Tu, Yixuan; Liu, Mei; Cheng, Qian; Zhang, Jian; Liu, Feiyang; Li, Xin (Frontiers in Medicine, 2023)
Purpose Metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) is gradually being used in hematological malignancy (HM) patients with suspected pulmonary infections. However, negative results are common and the clinical value and interpretation of such results in this patient population require further analysis. Methods Retrospective analysis of 112 HM patients with suspected pulmonary infection who underwent BALF mNGS and conventional microbiological tests. The final diagnosis, imaging findings, laboratory results and treatment regimen of 29 mNGS-negative patients were mainly analyzed. Results A total of 83 mNGS positive and 29 negative patients (15 true-negatives and 14 false-negatives) were included in the study. Compared to false-negative patients, true-negative patients showed more thickening of interlobular septa on imaging (p < 0.05); fewer true-negative patients had acute respiratory symptoms such as coughing or sputum production (p < 0.05) clinically; On the aspect of etiology, drug-related interstitial pneumonia (6/15, 40%) was the most common type of lung lesion in true-negative patients; on the aspect of pathogenesis, false-negative patients mainly missed atypical pathogens such as fungi and tuberculosis (8/14, 57.1%). Regarding treatment, delayed anti-infection treatment occurred after pathogen missing in mNGS false-negative patients, with the longest median time delay observed for anti-tuberculosis therapy (13 days), followed by antifungal therapy (7 days), and antibacterial therapy (1.5 days); the delay in anti-tuberculosis therapy was significantly longer than that in antibacterial therapy (p < 0.05). Conclusion For HMs patients with imaging showing thickening of interlobular septa and no obvious acute respiratory symptoms, lung lesions are more likely caused by drug treatment or the underlying disease, so caution should be exercised when performing BALF mNGS. If BALF mNGS is negative but infection is still suspected, atypical pathogenic infections should be considered.